Constructing 1 + 1 > 2 Photosensitizers Based on NIR Cyanine–Iridium(III) Complexes for Enhanced Photodynamic Cancer Therapy - Ziwei Wang; Weijin Wang; Qi Wu; Dongxia Zhu (Molecules)
Photosensitizers with high singlet oxygen (1O2) generation capacity under near-infrared (NIR) irradiation are essential and challenging for photodynamic therapy (PDT). A simple yet effective molecular design strategy is realized to construct 1 + 1 > 2 photosensitizers with synergistic effects by covalently integrating iridium complexes with cyanine via ether linkages, as well as introducing aldehyde groups to suppress non-radiative decay, named CHO−Ir−Cy. It is demonstrated that CHO−Ir−Cy successfully maintains the NIR absorption and emission originated from cyanine units and high 1O2 generation efficiency from the iridium complex part, which gives full play to their respective advantages while compensating for shortcomings. Density functional theory (DFT) calculations reveal that CHO−Ir−Cy exhibits a stronger spin–orbit coupling constant (ξ (S1, T1) = 9.176 cm−1) and a reduced energy gap (ΔE = −1.97 eV) between triplet excited states (T1) and first singlet excited states (S1) compared to parent Ir−Cy or Cy alone, directly correlating with its enhanced 1O2 production. Remarkably, CHO−Ir−Cy demonstrates superior cellular internalization in 4T1 murine breast cancer cells, generating substantially elevated 1O2 yields compared to individual Ir−Cy/Cy under 808 nm laser irradiation. Such enhanced reactive oxygen species production translates into effective cancer cell ablation while maintaining favorable biocompatibility, significant phototoxicity and negligible dark toxicity. This molecular engineering strategy overcomes the inherent NIR absorption limitation of traditional iridium complexes and ensures their own high 1O2 generation ability through dye–metal synergy, establishing a paradigm for designing metal–organic photosensitizers with tailored photophysical properties for precision oncology.